EXPERIENCE OF USING PLANET EARTH OBSERVATION DATA IN RETRAINING COURSES FOR EDUCATORS IN THE JUNIOR ACADEMY OF SCIENCES OF UKRAINE - Stanislav O. Dovgyi; Svitlana M. Babiichuk; Olha V. Tomchenko (Інформаційні технології і засоби навчання)
This paper discusses the background and presents the results of the first in Ukraine advanced training course for educators in Remote Sensing, “Fundamentals of Remote Sensing: History and Practice”, organized by the Geographic Information Systems and Remote Sensing Laboratory of the National Center, “Junior Academy of Sciences of Ukraine”. The Junior Academy of Sciences of Ukraine is a system of extracurricular education committed to the development and implementation of science education techniques. Currently, the Academy has more than 250,000 students working in 64 scientific areas. In 2018, the Junior Academy of Sciences of Ukraine received the status of Category 2 Science Education Center under the auspices of UNESCO and joined the network of Copernicus Academies. The Junior Academy of Sciences of Ukraine has been promoting the application of satellite imagery in education for over ten years. One of the outputs of this activity is the advanced training course for educators. This paper describes the online training course that was held in spring 2021 and 2022. The course was open to all interested teachers. A total of 41 educators from 13 regions of Ukraine have completed the training course in the span of two years. The paper describes the stages of special course organization, topics, and tools used in the lectures and case studies, including an overview of the data sources, such as EO-Browser, ArcGIS Online, Google my Maps, NASA Worldview and Google Earth, etc. The paper presents a detailed description of one of the hands-on case studies of water bodies in EO-Browser. It was established that the conducted special course promoted the educators’ interest in bringing Earth observation to classrooms. Increased number of GIS and Remote Sensing after-school clubs in the territorial branches of the Junior Academy of Sciences (from 1 in Kyiv as of 2019 to 9 in the regions as of 2022, namely in Poltava, Sumy, Volyn, Kyiv, Kirovohrad, Zakarpattia, Lviv, Kharkiv and Chernivtsi) is indicative of the course’s effectiveness.